Flexural and compressive properties of hybrid kenaf/silica nanopeprintss in epoxy composite - Bajuri, Farid; Mazlan, Norkhairunnisa; Ishak, Mohamad Ridzwan; Imatomi, Junichiro (Elsevier, 2016)
Kenaf fiber like other natural fibers is used as a sustainable form of material to fabricate composite. But natural fibers are generally weaker than synthetic fibers due to the porosity of the fibers making them grow weaker mechanically and physically as time passes. To improve the quality of kenaf reinforced composite, silica nanoparticles was introduced as a filler material. Silica nanoparticle is a material with high surface area contributing to its high interfacial interaction with the matrix resulting in the improvement of the matrix. In this work, the composites were fabricated via vacuum infusion process by creating a system in which the compressed randomly orientated kenaf mat are laid in. The silica nanoparticles are dispersed into the epoxy using a homogenizer at 3000 rpm for 10 minutes before being infused into the fibers. The results shows that generally the inclusion of hydrophobic silica nanoparticles had a detrimental effect on the mechanical properties. However, composites with 2 vol% silica had the best mechanical properties of specimens with silica nanoparticles included at 43.8 MPa and 3.05 GPa for flexural strength and flexural modulus, and 40.0 MPa and 1.15 GPa for compressive strength and compressive modulus, respectively.